Distribution of scytonemin in endolithic microbial communities from halite crusts in the hyperarid zone of the Atacama Desert, Chile - Vítek, Petr; Jehlička, Jan; Ascaso, Carmen; Mašek, Vlastimil; Gómez-Silva, Benito; Olivares, Héctor; Wierzchos, Jacek (FEMS microbiology ecology, 2014)
Scytonemin, a UV-screening molecule produced by certain Cyanobacteria to protect against harmful UV radiation, was studied in endolithic cyanobacterial colonies in the halite crust from one of the driest places on Earth - the hyperarid zone of the Atacama Desert. The distribution of the pigment within the evaporitic crust was studied in detail by various independent analytical methods: Raman spectroscopy (including Raman imaging); advanced microscopic observations (fluorescence microscopy, confocal laser scanning microscopy, low-temperature scanning electron microscopy); and spectrophotometric analyses. The differences in scytonemin biosynthesis were mapped within the colonized interior layers, which can be divided into scytonemin-rich and scytonemin-poor zones. A 532 nm laser for excitation proved to be an ideal excitation source with which to observe the relative content of scytonemin within a particular cell aggregate, as well as between different cell aggregates; based on the scytonemin/carotenoid Raman signal intensity ratio of selected corroborative bands for these two compounds. Significantly, scytonemin was found to accumulate within a decayed biomass in the surface portions of the halite crust. These were found to be highly enriched in both the absolute scytonemin content (as documented by UV/VIS spectrophotometry) and its content relative to other pigments associated with the cyanobacterial cells (e.g. carotenoids and chlorophyll).
Keywords: Cyanobacteria; Indoles; geologické sedimenty; sinice; indoly; Desert Climate; pouštní klima; fenoly; Phenols; Chile; Ultraviolet Rays; Carotenoids; chlorofyl; Light; halophile; Chroococcidiopsis; salt; adaptation strategy; Geologic Sediments; světlo; Chlorophyll; karotenoidy; ultrafialové záření